2021
DOI: 10.3991/ijet.v16i12.23327
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fuzzy Evaluation in Comprehensive Quality Evaluation of Higher Education Students

Abstract: Scientific and reasonable evaluation of the comprehensive quality of higher education students provides a guarantee for the pertinent development of quality education in colleges, and offers an aid for students to determine goals and directions of development. Therefore, this paper first constructs an evaluation index system (EIS) for the comprehensive quality of higher education students, and then builds up an evaluation model for that quality based on fuzzy comprehensive evaluation (FCE). The FCE algorithm w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The application results show that fuzzy comprehensive evaluation can reasonably evaluate the comprehensive quality of students from all aspects and levels. [3]. XU Yan suggested that high school students do a good job in ideological and political leadership and build a good student cadre is one of its important links.…”
Section: Introductionmentioning
confidence: 99%
“…The application results show that fuzzy comprehensive evaluation can reasonably evaluate the comprehensive quality of students from all aspects and levels. [3]. XU Yan suggested that high school students do a good job in ideological and political leadership and build a good student cadre is one of its important links.…”
Section: Introductionmentioning
confidence: 99%